RESPON PERTUMBUHAN TANAMAN BAWANG MERAH (Allium ascalanicum L.) TERHADAP PERLAKUAN PUPUK KOMPOS DAN NITROGEN - Abubakar, Abdarah (Jurnal Pertanian Agros, 2026)
Shallots (Allium ascalanicum L.) are a vegetable commodity with high economic value. Shallot productivity in West Nusa Tenggara (NTB) remains relatively low due to declining soil fertility. One way to increase shallot productivity is through the addition of soil fertility enhancers, such as compost, and fertilizer efficiency. This study aimed to determine the effect of compost, nitrogen fertilizer, and their interaction on shallot growth and yield. The experiment was conducted from May to August 2024 in the greenhouse of the Bima City Agriculture and Plantation Service. The experiment was designed using a factorial Completely Randomized Design consisting of two factors, namely the dose of Compost Fertilizer (3 levels) K0: 0 tons/ha without Compost Fertilizer, K1: 10 tons/ha, K2: 20 tons/ha, and the dose of Nitrogen (4 levels) N0: 0 kg/ha without Nitrogen, N1: 200 kg/ha, N2: 400 kg/ha. The results of the study showed that there was an interaction between the dose of Compost Fertilizer and nitrogen on the growth of plant height, number of leaves and number of cloves, where the dose of Compost Fertilizer was 20 tons/ha and nitrogen at 400 kg/ha gave the highest growth.